Prarancangan Pabrik Dimetil Eter Dari Tandan Kosong Sawit (TKS) Menggunakan Proses Indirect Synthesis Dengan Disain Alat Utama Reaktor DME - Ruth E. M. Sinaga; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The need for renewable energy increases with the number of business and process that require biogas and dimethyl ether as the raw material in the manufacturing process. Dimethyl ether is widely used as refregerant, propellant in aerosol products, solvent, and extraction agent. The main raw materials used in manufacture of dimethyl ether by indirect synthesis process is palm empty fruit bunch. This plant is planned to operate for 330 days per year and work continuously for 24 hours/day with capacity of 50,000 ton/year which will be established in Dumai, Riau. The remaining time for 1 year of the operation process is used for shutdown, plant maintenance, maintenance and repair of equipment. The design of the main equipment in this plant is Dimethyl Ether fixed bed reactor which functions to generate dimethyl ether by methanol dehydration process. Reactor is operated at a pressure of 5 Bar and a temperature of 250 °C. The economic analysis on the design of this plant shows that the dimethyl ether plant from palm empty fruit bunch is feasible to be established with the profits that the plant gets after tax is Rp. 1,807,080,722/year and the plant's Payback Period (PBP) is 2.29 years. Keywords: Dimethyl Ether, Economic Analysis, Empty Fruit Bunch, Plant Design